The Effect of Black Cumin (Nigella Sativa) on Breastfeeding Mothers - Zakaria, Rabia; Astuti, Siti Choirul Dwi (JURNAL INFO KESEHATAN, 2022)
Breast milk is the best nutrient to reduce the pain in nursing mothers and death in infants. However, for nursing mothers, too little milk volume is the cause of problems occurring during the breastfeeding process. Thus, mothers who breastfeed should consume foods that can increase the breast milk volume. One food frequently consumed by mothers to increase breast milk is honey. In fact, natural honey is challenging to discover, and the price is also high which makes it as an obstacle. A more economical alternative is required, one of which is black cumin. It is easy to obtain and the price is also affordable. Black cumin also contains galactagogue to increase prolactin that influences breast milk production. The objective of this study is to identify the effect of black cumin on the volume of breast milk. The study was a randomized controlled trial involving 60 breastfeeding mothers divided into intervention groups and control groups. The intervention group was provided 15 grams of black cumin brewed with 1000C boiling water as much as 200 ml, and the control group was assigned 15 grams of pure honey brewed boiling 1000C as much as 200 ml. Intervention and control were administered on the second day to the day of completion after giving birth. They were measuring instruments which accustomed to measure breast milk pumps. Bivariate analysis employing the Wilcoxon and Mann Whitney tests presented a significant difference between the volume of breast milk (p = 0.001) of the control and intervention groups. This study recommends the application of black cumin as a strategy to increase the volume of breast milk in nursing mothers.